2011
DOI: 10.11646/zootaxa.2911.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Brachyuran crabs of the family Macrophthalmidae Dana, 1851 (Decapoda: Brachyura: Macrophthalmidae) of the Persian Gulf

Abstract: The family Macrophthalmidae Dana, 1851, is one of the best represented brachyuran groups in intertidal habitats in the Persian Gulf. Nine species from two subfamilies are reported from the gulf and the adjacent Gulf of Oman, mainly inhabiting intertidal soft substrates. The subfamily Ilyograpsinae Števcic, 2005, is represented by Ilyograpsus rhizophorae Barnard, 1950, erroneously recorded as I. paludicola (Rathbun, 1909). Eight species of the subfamily Macrophthalminae Dana, 1851, have been recorded from the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Other species, such as Dynamenella granulata, and Atarbolana exoconta, are widely distributed along the northeastern coast of the Gulf and along the Pakistani coast. Their distribution pattern is similar to some brachyuran decapods as suggested by Apel and Türkay (1999) and Naderloo et al (2011). According to this distribution pattern, the fiddler crab fauna of the southern and western Gulf is similar in East Africa, the Gulf of Aden, and the Red Sea.…”
Section: Discussionsupporting
confidence: 78%
“…Other species, such as Dynamenella granulata, and Atarbolana exoconta, are widely distributed along the northeastern coast of the Gulf and along the Pakistani coast. Their distribution pattern is similar to some brachyuran decapods as suggested by Apel and Türkay (1999) and Naderloo et al (2011). According to this distribution pattern, the fiddler crab fauna of the southern and western Gulf is similar in East Africa, the Gulf of Aden, and the Red Sea.…”
Section: Discussionsupporting
confidence: 78%
“…Specimens were collected by hand, fixed in 98% ethanol, and then were transferred to Senckenberg Research Institute and Natural History Museum for species identification and taxonomic classification. The species were identified using following identification keys(Naderloo, 2017;Naderloo et al, 2011;Ng et al, 2008) and were confirmed by Dr. Mendoza from National University of Singapore (FigureS2-S7), which belonged to 10 species and two genera (Figure1; FigureS2-S7). Some key features for studied taxa of mangrove crabs here are included in FigureS2-S7.…”
mentioning
confidence: 88%
“…The environmental conditions including extreme salinity and temperature fluctuations of the Persian Gulf have created diverse marine habitats with remarkably high biodiversity of particular taxa, such as brachyuran crabs (Apel & Türkay, 1999;Naderloo & Schubart, 2009). Among intertidal brachyuran fauna of the Persian Gulf, ocypodid crabs are considered as its major element (Apel & Türkay, 1999;Naderloo et al, 2011;Sharifian et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Macrophthalmus depressus is less abundant and lives close to the shore in silty sediments (Bom et al, 2020). These different crab species and tidal habitats may be associated with different burrow morphology but this remains unaccounted for (Naderloo et al 2011).…”
Section: Introductionmentioning
confidence: 99%